Targeted inhibition of tumor-derived exosomes as a novel therapeutic option for cancer - Li, Ye; Chen, Zhuo-Kun; Duan, Xu; Zhang, He-Jing; Xiao, Bo-Lin; Wang, Kui-Ming; Chen, Gang (Experimental & molecular medicine, 2022)
Mounting evidence indicates that tumor-derived exosomes (TDEs) play critical roles in tumor development and progression by regulating components in the tumor microenvironment (TME) in an autocrine or paracrine manner. Moreover, due to their delivery of critical molecules that react to chemotherapy and immunotherapy, TDEs also contribute to tumor drug resistance and impede the effective response of antitumor immunotherapy, thereby leading to poor clinical outcomes. There is a pressing need for the inhibition or removal of TDEs to facilitate the treatment and prognosis of cancer patients. Here, in the present review, we systematically overviewed the current strategies for TDE inhibition and clearance, providing novel insights for future tumor interventions in translational medicine. Moreover, existing challenges and potential prospects for TDE-targeted cancer therapy are also discussed to bridge the gaps between progress and promising applications. Cancer therapy: Interrupting messages sent by tumors Inhibiting or removing tumor-derived exosomes (TDEs), tiny membrane-bound packets of DNA, RNA, and proteins secreted by tumors, may improve cancer therapies. TDEs can suppress the body’s immune response, promote tumor progression and spread, and reduce efficacy of cancer drugs and immunotherapy. Gang Chen at Wuhan University, China, and co-workers have reviewed ways to remove or inhibit production of TDEs. They report that disruption of the genes for production of TDEs, drugs that inhibit TDE secretion, and removal of TDEs via plasma exchange or dialysis are all being investigated and show promise for reducing patient TDE load, thereby increasing the efficacy of anti-cancer drugs and immunotherapy. Future challenges include reducing side effects and finding less invasive ways to filter out TDEs. Gaining a better understanding of TDEs may help to improve therapies for many types of cancer.